2018
DOI: 10.1101/375493
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Point of care influenza testing using Alere-i Influenza A & B assay: a practical assessment

Abstract: 23We assessed the utility of the Alere i Influenza A & B point of care influenza test POCIT) with laboratory testing using RT-PCR. 270 adult hospital patients had both 25Ai-POCIT and laboratory influenza tests conducted on the same sample. Overall, 30% 26 and 32% influenza tests were positive by Ai-POCIT and RT-PCR, respectively. The 27 sensitivity of the Ai-POCIT for influenza A, influenza B and any influenza were 93%, 28 100%, and 95%, respectively. Specificity was 100% for both viruses, but an 11% test 29 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…ID NOW). A number Open Access BMC Research Notes *Correspondence: sjpoconnell@bonsecours.ie 2 Shannon Applied Biotechnology Centre, Institute of Technology Tralee, Tralee, Co. Kerry, Ireland Full list of author information is available at the end of the article of studies have been reported outlining the performance of the Alere I POCT (now known as Abbott ID NOW) NAAT versus laboratory based methods such as thermocycler rtPCR and viral culture for Influenza testing [5][6][7][8][9][10][11][12][13][14][15][16]. These studies have reported influenza A sensitivity in the range of 66-100% and specificity of 55-100%, while for influenza B sensitivity ranged from 45 to 100% and specificity 54-100%.…”
Section: Introductionmentioning
confidence: 99%
“…ID NOW). A number Open Access BMC Research Notes *Correspondence: sjpoconnell@bonsecours.ie 2 Shannon Applied Biotechnology Centre, Institute of Technology Tralee, Tralee, Co. Kerry, Ireland Full list of author information is available at the end of the article of studies have been reported outlining the performance of the Alere I POCT (now known as Abbott ID NOW) NAAT versus laboratory based methods such as thermocycler rtPCR and viral culture for Influenza testing [5][6][7][8][9][10][11][12][13][14][15][16]. These studies have reported influenza A sensitivity in the range of 66-100% and specificity of 55-100%, while for influenza B sensitivity ranged from 45 to 100% and specificity 54-100%.…”
Section: Introductionmentioning
confidence: 99%
“…ID NOW). A number of studies have been reported outlining the performance of the Alere I POCT (now known as Abbott ID NOW) NAAT versus laboratory based methods such as thermocycler rtPCR and viral culture for Influenza testing [5][6][7][8][9][10][11][12][13][14][15][16].These studies have reported influenza A sensitivity in the range of 66-100% and specificity of 55-100%, while for influenza B sensitivity ranged from 45-100% and specificity 54-100%. The studies comparing ID NOW with the GeneXpert have previously used nasopharyngeal swabs in viral transport medium (VTM) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…ID NOW). A number of studies have been reported outlining the performance of the Alere I POCT (now known as Abbott ID NOW) NAAT versus laboratory based methods such as thermocycler rtPCR and viral culture for Influenza testing [5][6][7][8][9][10][11][12][13][14][15][16].These studies have reported influenza A sensitivity in the range of 66-100% and specificity of 55-100%, while for influenza B sensitivity ranged from 45-100% and specificity 54-100%. The studies comparing ID NOW with the GeneXpert have previously used nasopharyngeal swabs in viral transport medium (VTM) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%